Безпекові проекти МВС України як основа забезпечення стабільності та розвитку держави - Бугайчук, К. Л.; Buhaichuk, K. L.; Костянтин Бугайчук (Problems of the development of science and the view of society : proceedings of the XI International Scientific and Practical Conference ( Graz, Austria; 21-24 March 2023). - Graz, 2023. - Р. 119-123, 2023)
У тезах досліджено сутність організації та реалізації проєктів МВС України, спрямованих на формування безпекового середовища держави та їх вплив на загальну криміногенну ситуацію в Україні.

The thesis examines the essence of the organization and implementation of projects of the Ministry of Internal Affairs of Ukraine, aimed at forming the security environment of the state and their impact on the general criminogenic situation in Ukraine.

В тезисах исследована сущность организации и реализации проектов МВД Украины, направленных на формирование среды обитания государства и их влияние на общую криминогенную ситуацию в Украине.
Keywords: Україна; безпекове середовище; безпека; МВС України; Національна поліція України; security environment; security; Ministry of Internal Affairs of Ukraine; National Police of Ukraine; strategy; project; безпекові проекти МВС України; безопасность; Национальная полиция Украины